Systems engineering with SysML/UML modeling, analysis, design - Weilkiens, Tim. (Amsterdam ; Boston : Morgan Kaufmann OMG Press/Elsevier, 2007)
UML, the Universal Modeling Language, was the first language designed to fulfill the requirement for "universality." However, it is a software-specific language, and does not support the needs of engineers designing from the broader systems-based perspective. Therefore, SysML was created. It has been steadily gaining popularity, and many companies, especially in the heavily-regulated Defense, Automotive, Aerospace, Medical Device and Telecomms industries, are already using SysML, or are plannning to switch over to it in the near future. However, little information is currently available on the market regarding SysML. Its use is just on the crest of becoming a widespread phenomenon, and so thousands of software engineers are now beginning to look for training and resources. The proposed book will provide an introduction to SysML, and instruction on how to implement it, for all these new users. *The first available book on SysML in English *Insider information! The author is a member of the SysML working group and has written sections of the specification *Special focus comparing SysML and UML, and explaining how both can work together.
1. Introduction; 2. Process SYSMOD; 3. SysML- Systems Modeling Language; 4. UML- Unified Modeling Language; 5. Systems-Engineering-Profile; Appendices, Glossary, and Literature References.
Includes bibliographical references (p. 295-297) and index.
Keywords: Systems engineering; SysML (Computer science); UML (Computer science); Electronic books